2019
DOI: 10.1037/pas0000629
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factor structure of the Self-Compassion Scale in 20 diverse samples: Support for use of a total score and six subscale scores.

Abstract: This study examined the factor structure of the Self-Compassion Scale (SCS) using secondary data drawn from 20 samples (N = 11,685)-7 English and 13 non-English-including 10 community, 6 student, 1 mixed community/student, 1 meditator, and 2 clinical samples. Self-compassion is theorized to represent a system with 6 constituent components: self-kindness, common humanity, mindfulness and reduced self-judgment, isolation and overidentification. There has been controversy as to whether a total score on the SCS or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
310
2
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(353 citation statements)
references
References 108 publications
21
310
2
20
Order By: Relevance
“…Each subscale has been shown to mediate the effect of a self-compassion intervention on reduced depression in BCa patients (Boyle, Stanton, Ganz, Crespi, Bower, et al, 2018). In a large cross-national study, Neff et al (2019) showed that Self-Compassion Scale items form distinct factors that correspond to Neff's (2003b) original subscales. We used subscale rather than full-scale scores as predictors.…”
Section: Self-compassionmentioning
confidence: 99%
“…Each subscale has been shown to mediate the effect of a self-compassion intervention on reduced depression in BCa patients (Boyle, Stanton, Ganz, Crespi, Bower, et al, 2018). In a large cross-national study, Neff et al (2019) showed that Self-Compassion Scale items form distinct factors that correspond to Neff's (2003b) original subscales. We used subscale rather than full-scale scores as predictors.…”
Section: Self-compassionmentioning
confidence: 99%
“…While these factors are of interest and are linked to mental health difficulties and well-being, the division into positive and negative factors and the use of the scale as a single score is controversial. [9][10][11][12]. Many researchers suggest the use of two factors not one [13].…”
Section: Introductionmentioning
confidence: 99%
“…This increased our skeptical scientific attitude regarding the SCS: we did not understand why researchers did not see the obvious point that we were making regarding this measure, and hence, we began to share our critical thoughts with the scientific community (Muris 2016;Muris and Petrocchi 2017;Muris et al 2016bMuris et al , 2019b. However, the developer of the SCS (Neff 2016a(Neff , b, 2019 maintained that the scale in its original form provides a good index of self-compassion.…”
mentioning
confidence: 99%